Contemporary society challenges of integrative teaching - Jovanović, Marija M; Kovčić, Vesna S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
This paper discusses the characteristics of integrative teaching as an innovative teaching model which creates opportunities for comprehensive development of the student's personality through the adoption of comprehensive knowledge and development of functional abilities of students. Based on the principle of functional connectivity of meaningful, cognitive, psychological, organizational and sociological aspects of teaching, integrative teaching offers many opportunities for good quality educational activities. However, the complexity that arises from the abovementioned traits of integrative teaching entails some difficulties in the process of its planning, programming and implementation. It is important for the teaching process to have a good knowledge of the essential characteristics and values of integrative teaching and a willingness to use successful didactic and methodical tools to overcome potential difficulties.In order to systematically emphasize the current challenges of integrative teaching, this paper approached this problem from the aspect of: theoretical definitions, didactic values, disadvantages, the implementation ofintegrative teaching in schools, and how integrative teaching helps students to acquire knowledge.
Keywords: didactic values; Implementation; knowledge; Learning outcomes; integrative teaching